2002
DOI: 10.1210/rp.57.1.195
|View full text |Cite
|
Sign up to set email alerts
|

Novel Signaling Pathways That Control Ovarian Follicular Development, Ovulation, and Luteinization

Abstract: Mutations in the androgen receptor (AR) gene cause a range of phenotypic abnormalities of male sexual development. At one end of the spectrum are individuals with complete androgen insensitivity (complete testicular feminization) who exhibit normal breast development and female external genitalia. At the other extreme are individuals with male phenotypes that are characterized by either subtle undervirilization or infertility. Studies in a number of different laboratories have identified mutations of the AR ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
204
2
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 365 publications
(221 citation statements)
references
References 133 publications
6
204
2
9
Order By: Relevance
“…More recent studies though indicate that insulin and IGFs can bind hybrid receptors of IR and IGFR monomers, resulting in greater activity spectra than previously assumed (29)(30)(31)(32). In addition to their mitogenic activities, IGFs produced in the nervous system of mammals also regulate reproduction and steroid hormone secretion (36,37), suggesting an interesting parallel with invertebrates given results of the current study. Less clear is whether mosquito and other insect ILPs have overlapping activities and how activity may be regulated when only one IR/IGFR homolog and fewer isoforms of downstream signaling components are present (8,9).…”
Section: Discussionsupporting
confidence: 54%
“…More recent studies though indicate that insulin and IGFs can bind hybrid receptors of IR and IGFR monomers, resulting in greater activity spectra than previously assumed (29)(30)(31)(32). In addition to their mitogenic activities, IGFs produced in the nervous system of mammals also regulate reproduction and steroid hormone secretion (36,37), suggesting an interesting parallel with invertebrates given results of the current study. Less clear is whether mosquito and other insect ILPs have overlapping activities and how activity may be regulated when only one IR/IGFR homolog and fewer isoforms of downstream signaling components are present (8,9).…”
Section: Discussionsupporting
confidence: 54%
“…Similarly, granulosa cells are epithelial-derived cells, and the adenomatosis polyposis coli (Apc) gene is known to regulate epithelial cell migration, mitosis and differentiation (McCartney & Nathke 2008). In addition, APC regulates β-catenin in the Wnt/frizzled/β-catenin signaling pathway, and this signaling pathway has been shown to be important for ovarian and follicular development (Richards et al 2002, Ricken et al 2002. Ubiquitination is also important for proper functioning of the Wnt/β-catenin/APC pathway (Voutsadakis 2008), and both Nedd4 and Ube4a are genes regulated by NT3 treatment that are involved in ubiquitination (Caren et al 2006, Gay et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation with LH of matured preovulatory follicles induces the differentiation of granulosa cells to luteinized granulosa cells [25]. In addition, it has been demonstrated that several molecules, which are up-regulated with LH stimulation, are involved in granulosa cell differentiation and luteinization.…”
Section: Discussionmentioning
confidence: 99%